EDUCATION AS A SPACE OF INTERNALIZATION OF LEGAL VALUES: A PEDAGOGICAL APPROACH IN THE FORMATION OF CHARACTER - Rukmono, Indra; Dhayinta, Shellya Tanaya (EDUCATUM: Scientific Journal of Education, 2026)
Education has a strategic role in shaping the legal awareness and character of students as the foundation of the life of the nation and state. However, the current educational reality still shows a gap between the mastery of legal knowledge and the internalization of legal values in the real behavior of learners. This study aims to analyze conceptually how education can function as a space for internalization of legal values through a pedagogical approach in character formation. This research uses the design of literature studies with a systematic literature review (SLR) approach to scientific articles, academic books, and reputable publications relevant to education, legal values, pedagogy, and character education, especially the last five years. The analysis was carried out thematically and conceptually to identify patterns, pedagogical approaches, as well as the implications of the internalization of legal values in educational practice. The results showed that the internalization of legal values in education is effective when done through reflective, contextual, and participatory pedagogical approaches, such as character education, critical pedagogy, and experiential learning. Legal values such as Justice, responsibility, honesty, and respect for the rights of others are proven to contribute significantly to the formation of the character of learners when consistently integrated in the curriculum, learning practices, and school culture. This study confirms that education not only serves as a means of transmitting knowledge, but also as a space for moral and social transformation in building the legal character of the younger generation